2017
DOI: 10.1007/s11103-017-0643-3
|View full text |Cite
|
Sign up to set email alerts
|

The Glycine soja NAC transcription factor GsNAC019 mediates the regulation of plant alkaline tolerance and ABA sensitivity

Abstract: Overexpression of Gshdz4 or GsNAC019 enhanced alkaline tolerance in transgenic Arabidopsis. We proved that Gshdz4 up-regulated both GsNAC019 and GsRD29B but GsNAC019 may repress the GsRD29B expression under alkaline stress. Wild soybean (Glycine soja) has a high tolerance to environmental challenges. It is a model species for dissecting the molecular mechanisms of salt-alkaline stresses. Although many NAC transcription factors play important roles in response to multiple abiotic stresses, such as salt, osmotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 62 publications
1
32
0
Order By: Relevance
“…These posttranscriptional mechanisms act together to activate AHA2, then promotes root H + efflux, thereby activating SOS1 Na + /H + antiporter and other adaptive responses 18,25 . Moreover, previous studies have also suggested that the transcript levels of some PM-H + -ATPase increased under stress conditions, e.g., phosphorus deficiency increases the transcript levels of AHA2 and AHA7 26 , iron deficiency increases the expression of AHA2 and AHA7 27 , salt stress upregulates the transcript levels of AHA2 28 . These observations indicate that the transcriptional regulation of PM-H + -ATPase is also important for the regulation of root H + efflux under stress conditions, nevertheless, the mechanism remains largely unknown.…”
mentioning
confidence: 94%
“…These posttranscriptional mechanisms act together to activate AHA2, then promotes root H + efflux, thereby activating SOS1 Na + /H + antiporter and other adaptive responses 18,25 . Moreover, previous studies have also suggested that the transcript levels of some PM-H + -ATPase increased under stress conditions, e.g., phosphorus deficiency increases the transcript levels of AHA2 and AHA7 26 , iron deficiency increases the expression of AHA2 and AHA7 27 , salt stress upregulates the transcript levels of AHA2 28 . These observations indicate that the transcriptional regulation of PM-H + -ATPase is also important for the regulation of root H + efflux under stress conditions, nevertheless, the mechanism remains largely unknown.…”
mentioning
confidence: 94%
“…The whole genome of G. soja has been sequenced and one novel gene ( GmCHX1 ) related with abiotic stresses was identified by comparative genomics (Qi et al, ). Nevertheless, we also reported a dozen of wild soybean genes with resistance to abiotic stresses in plants (Cao et al, , ; Duanmu et al, ; Jia et al, ; Yu et al, , ). However, the functions of SnRK1 kinases (defined as GsSnRK1s) in wild soybean are still largely unknown.…”
Section: Introductionmentioning
confidence: 94%
“…In rice for example, overexpression of a NAC TF encoding gene, SNAC1 resulted in increased yields and increased tolerance to drought in transgenic plants (Hu et al, 2006). Overexpression of a Glycine soja NAC TF designated as GsNAC019 in transgenic Arabidopsis resulted in plants that were tolerant to alkaline stress at both the seedling and mature stages although the transgenic plants had reduced sensitivity to Abscisic acid (ABA) (Cao et al, 2017). Similarly, functional analysis of a Pyrus betulifolia NAC TF gene designated as PbeNAC1, revealed that this gene is involved in the regulation of cold and drought stress tolerance (Jin et al, 2017).…”
Section: Functions Of Transcription Factorsmentioning
confidence: 99%